Spectroscopic and biological activity studies on tridentate Schiff base ligands and their transition metal complexes - Abd El-Halim, Hanan Farouk; Omar, Mohamed Mohamed; Mohamed, Gehad Genidy; El-Ela Sayed, Mohsen Abou (European Journal of Chemistry, 2011)
Schiff base ligands are prepared via condensation of pyridine-2,6-dicarboxaldehyde with 2-aminothiophenol (H2L1) and 2-aminobenzoic acid (H2L2), respectively. The ligands are characterized based on elemental analysis, mass, IR and 1H NMR spectra. Metal complexes are reported and characterized based on elemental analyses, IR, 1H NMR, solid reflectance, magnetic moment, molar conductance, and thermal analyses (TG, DTG and DTA). The molar conductance reveals that all the metal chelates are non-electrolytes except Th(IV) H2L2 complex which is 1:1 electrolyte . IR spectra show that H2L1 and H2L2 ligands behave as neutral tridentate ligands and bind to the metal ions via the two azomethine N and pyridine N. From the magnetic and solid reflectance spectra, it is found that the geometrical structures of these complexes are octahedral (Cr(III)- and Fe(III)-H2L1 and H2L2, Th(IV)-H2L2 and Mn(II)-H2L1 complexes) and triagonal bipyramidal (Co(II), Ni(II), Cu(II), Cd(II) and UO2(II)-H2L1 and H2L2 and Mn(II)-H2L2 complexes). The thermal behaviour of these chelates is studied using TG and DTA techniques and the activation thermodynamic parameters are calculated using Coats-Redfern method. The synthesized ligands and their metal complexes were screened for their biological activity against bacterial species (Escherichia coli, P. vulgavis, B. subtilis and S. pyogones) and fungi (F. solani, A. niger and A. liavus). The activity data show that the metal complexes have antibacterial and antifungal activity more than the parent Schiff base ligands against one or more bacterial or fungi species.